The International Monetary Fund and Latin America The Argentine Puzzle in Context - Kedar, Claudia (Temple University Press, 2013)
The International Monetary Fund (IMF) has played a critical role in the global economy since the postwar era. But, claims Claudia Kedar, behind the strictly economic aspects of the IMF's intervention, there are influential interactions between IMF technocrats and local economists-even when countries are not borrowing money. In The International Monetary Fund and Latin America, Kedar seeks to expose the motivations and constraints of the operations of both the IMF and borrowers. With access to never-before-seen archive materials, Kedar reveals both the routine and behind-the-scenes practices that have depicted International Monetary Fund-Latin American relations in general and the asymmetrical IMF-Argentina relations in particular. Kedar also analyzes the "routine of dependency" that characterizes IMF-borrower relations with several Latin American countries such as Chile, Peru, and Brazil. The International Monetary Fund and Latin America shows how debtor countries have adopted IMF's policies during past decades and why Latin American leaders today largely refrain from knocking at the IMF's doors again.